Coping with climate change: Three insights for research, intervention, and communication to promote adaptive coping to climate change. (October 2020) - Mah, Andrea Y.J.; Chapman, Daniel A.; Markowitz, Ezra M.; Lickel, Brian
Highlights: Insights for communication to improve coping with climate change are provided. Communication principles are suggested for the climate change coping context. Climate change will have diverse impacts on peoples' stress and coping responses. Individual resilience is linked to ecosystem and community resilience. Abstract: Climate change poses a major threat to human well-being and will be the root cause of a variety of stressors in coming decades. Psychologists have an important role to play in developing interventions and communication strategies to help people understand and cope with climate change impacts. Through a review of the literature, we identify three guiding insights for strategies to promote adaptive coping and resilience to climate change stress. First, it is unlikely that one single "correct" or "best" way of communicating about adaptive coping with climate change exists, but there are established best practices communicators can follow. Second, in implementing these best practices, practitioners must attend to the impact of variability in the nature of different kinds of stress caused by climate change, as well as individual differences in how people chronically respond to stressors. Third, because individuals, communities, and ecosystems are interconnected, work on adaptive coping to climate change must address individual coping in the context of community and ecosystem resilience. These insights from psychological science can be leveraged to promote human flourishing despite increasing stressors posed by climate change.